Electrochemical Polymerization of Ambipolar Carbonyl-Functionalized Indenofluorene With Memristive Properties - Figa, Viviana; Usta, Hakan; Macaluso, Roberto; Salzner, Ulrike; Ozdemir, Mehmet; Kulyk, Bohdan; Bruno, Maurizio (Elsevier, 2019)
Carbonyl-functionalized indenofluorene was electropolymerized with a high faradaic efficiency of 85% and the solid state properties of the resulting polymeric thin films were investigated. They displayed modular optical properties depending on their oxidation state. The approach used for inorganic semiconductors was applied to polyindeonofluorene derivative. Mott-Schottky analysis evidenced a switching from p-type to n-type electrical conduction, suggesting an ambipolar behaviour of the polymer. As an application, flexible organic memristors were fabricated and resistive switching properties were observed.
Usta, Hakan/0000-0002-0618-1979; Krupka, Oksana/0000-0002-7891-7391;
Keywords: Indenofluorene Derivatives; Electrochemical Polymerization; Organic Semiconductors; Organic MeMRIstors